Evidence for electroweak production of W±W±jj in pp collisions at √s = 8 TeV with the ATLAS Detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Brandt, Oleg; Colombo, Tommaso; Davygora, Yuriy; Dietzsch, Thorsten; Dunford, Monica; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; Kasieczka, Gregor; et al. (Physical review letters, 2014)
This Letter presents the first study of W±W±jj, same-electric-charge diboson production in associationwith two jets, using20.3fb−1of proton-proton collision data atffiffiffisp¼8TeV recorded by the ATLASdetector at the Large Hadron Collider. Events with two reconstructed same-charge leptons (e±e±, e±μ±, and μ±μ±) and two or more jets are analyzed. Production cross sections are measured in two fiducial regions, with different sensitivities to the electroweak and strong production mechanisms. First evidence for W±W±jj production and electroweak-only W±W±jj production is observed with a significance of 4.5 and 3.6 standard deviations, respectively. The measured production cross sections are in agreement with standard model predictions. Limits at 95% confidence level are set on anomalous quartic gauge couplings.